COVID-19, Social Policy and Care: A Complex Set of Processes and Outcomes - Daly, Mary (Frontiers in Sociology, 2022)
Frontiers abstract This paper looks at the 2020 period of COVID-19 and especially the first months through the lens of public support for care. It covers the policy responses to both care for young children and frail, ill or disabled adults and develops an understanding of care as welfare-related activity focused on practices and resources oriented to meeting care-related need. The article’s over-arching research question centres around how European countries responded to the 2020 pandemic, especially in regard to the types of care need that were recognized, the resources committed, the actors/agency that was supported or taken for granted and the values that underpinned the responses. What we find from the review is that, while care assumed a strong place in public rhetoric, this was not reflected in greater public resourcing of with care for young children or long-term care. Instead, care for children was refamilialized and long-term care was under-resourced and relegated to a secondary position, also in many ways dependent on the private agency of individuals. In sum, the pandemic spearheaded some reversion to old practices and the opportunity to invest in care as both a human need and valued activity and put in place badly-needed reform was not taken.